The role of lighter oil components on CO2-induced swelling and pressure decay dynamics under reservoir conditions - Bilal Zulfiqar; Moh’d Amro; Helmut Geistlinger (Chemical Thermodynamics and Thermal Analysis, 2025)
CO2 injection into geological formations is considered as technologically advanced and economically feasible approach that combines both enhanced oil recovery (EOR) and CO2 sequestration. The composition of crude oil, in particular the distinction between its lighter and heavier components, plays an important role in controlling the essential physico-chemical properties such as volume increase, miscibility, solubility, density change, diffusion, interfacial tension, and their complex interrelationship. To the best of our knowledge, this is the first systematic study conducted to investigate the impact of lighter crude oil components on oil swelling phenomena and pressure decay dynamics in a CO2-crude oil system at elevated pressures and temperatures encountered in reservoirs, using combined micro-CT-, pressure-decay experiments and modeling.We proposed a conceptual model which assumes that the phenomena of CO2-induced oil volume increase is controlled by the proportion of lighter components (C1-C10) in crude oil, and consistently explains the time dependence of the oil volume increase. Our micro-CT experimental results verify this model and demonstrate that the oil volume increases with an increase in the lighter components in crude oil. The thickness of the oil layer (volumetric increase) increased significantly from 1.8 mm to 10.2 mm by varying the lighter components in the oil from 20 wt % to 100 wt %. An ordered short-chain alkane-CO2-alkane structure forms at the CO2-crude oil interface through CO2 binding bridges and increases the oil volume until the CO2-crude oil system reaches partitioning equilibrium.Concurrently, we conducted independent pressure decay analysis and evaluated key kinetic parameters for varying compositions of crude oil. With an increasing proportion of lighter components in the crude oil, we observed a significant increase in the concentration profile of dissolved CO2 within the crude oil phase, and the partition equilibrium shifted toward higher dissolved CO2 concentrations. The Henry constant markedly decreased from 11.3 to 2.4 as the percentage of lighter components in the crude oil increased from 20 wt % to 100 wt %. The diffusion coefficient remained nearly constant, i.e., insensitive to variations in the lighter crude oil components. From a broader perspective, our comprehensive study of crude oil swelling due to CO2 injection has profound relevance in optimizing CO2-EOR strategies and enhancing CO2 sequestration efficiency.